2014
DOI: 10.1517/17425247.2014.915310
|View full text |Cite
|
Sign up to set email alerts
|

Solid lipid nanoparticles of diethylcarbamazine citrate for enhanced delivery to the lymphatics:in vitroandin vivoevaluation

Abstract: Targeting of DEC to the lymphatics is possible through SLNs and the retention time in the lymphatics can also be enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Interestingly, inhibiting phagocytosis using dextran as an adjuvant increased both lymphatic uptake and residence time of PEGylated colloids. 21 PEGylation can be applied in developing various nanoparticulate carriers like dendrimers, 10 PRINT (particle replication in nonwetting templates) hydrogels, 28 magnetic carbon nanotubes with PEG groups, 29 solid lipid nanoparticles, 3 polymeric nanoparticles, 24 liposomes, 25 and so on. Furthermore, a glance at a few of the promising nanopharmaceuticals in clinical use or undergoing trials like Oncaspar (PEGylated l-asperginase for acute lymphoblastic leukemia), Genexol (PEGylated block polymer containing an anticancer drug for metastatic breast cancer), and Lipo-dox and ThermoDox (PEGylated liposomal forms of doxorubicin) highlights the utility of PEGylation.…”
Section: Pegylation: Gateway For Lymphatic Targetingmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, inhibiting phagocytosis using dextran as an adjuvant increased both lymphatic uptake and residence time of PEGylated colloids. 21 PEGylation can be applied in developing various nanoparticulate carriers like dendrimers, 10 PRINT (particle replication in nonwetting templates) hydrogels, 28 magnetic carbon nanotubes with PEG groups, 29 solid lipid nanoparticles, 3 polymeric nanoparticles, 24 liposomes, 25 and so on. Furthermore, a glance at a few of the promising nanopharmaceuticals in clinical use or undergoing trials like Oncaspar (PEGylated l-asperginase for acute lymphoblastic leukemia), Genexol (PEGylated block polymer containing an anticancer drug for metastatic breast cancer), and Lipo-dox and ThermoDox (PEGylated liposomal forms of doxorubicin) highlights the utility of PEGylation.…”
Section: Pegylation: Gateway For Lymphatic Targetingmentioning
confidence: 99%
“…Studies have revealed that although PEGylation improved lymphatic uptake, it reduced the retention time of colloids. 2,3,10,33 The authors hypothesized that the poor retention of the colloids in the lymph nodes is due to the smaller size and extreme hydrophilic nature of PEGylated colloids. These colloids probably escaped through the spaces present between the lymphatic capillary cells because of their smaller size.…”
Section: Size-dependent Retention In Lymphaticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sustained release phase of the drug is also not prolonged for longer hours because of the smaller diameter of the particles, which provides a larger surface area for the drug-loaded particles. 65,66 stability of slN-DaP and M-slN-DaP…”
mentioning
confidence: 99%